EARLY ONSET DIABETES - GENETIC AND HORMONAL ANALYSIS IN PAKISTANI POPULATION - Wahid, Maryam; Kamran, Mohammad (Journal of Ayub Medical College Abbottabad, 2016)
Background: Mitochondrial DNA mutation and hormonal imbalance is involved in the pathogenesis of early onset diabetes but data is lacking in Pakistani population. The study was planned to delineate the clinical presentation of early onset diabetes with possible hormonal and genetic etiological factors and aascertain the possible etiological role of insulin and glucagon in these patients either on oral hypoglycaemic or subcutaneous insulin therapy. Methods: Retrospective, analytical case control study with conventional sampling technique carried at Centre for Research in Experimental and Applied Medicine (CREAM) affiliated with the department of Biochemistry and Molecular Biology, Army Medical College Rawalpindi from Dec 2006 to July 2011. Study included the patients (20-35 years of age) with early onset diabetes on oral hypoglycemic (n=240), insulin therapy (n=280), and compared with non-diabetic healthy controls (n=150). A fragment surrounding tRNALeu (UUR) gene was amplified by AmpliTaq from mtDNA which was extracted from peripheral blood leucocytes. Then it was subjected to restriction endonucleases, ApaI for A3242G mutation and HaeIII for G3316A mutation detection. Plasma glucose, glycosylated Hb, osmolality, insulin and glucagon levels along with ABGs analysis was also done. Results: Non diabetic controls comprised of 51% males and 49% females, diabetics on oral hypoglycemic 60% males and 40 % females and on insulin therapy 54% males and 46% females. Insulin dependent diabetics had statistically significant hyperglucagonemia, acidemia and bicarbonate deficit. MtDNA A3242G and G3316A mutations were not detected. Conclusion: relative hyperglucagonemia and acidemia in Insulin dependent diabetics was a potent threat leading to DKA. The absence of two mtDNA mutations in ND1 gene rules out the possibility of involvement of these mutations in early onset diabetes in Pakistani population. Keywords: MtDNA; Mt-ND1 gene; NADH dehydrogenase; Hyperglucagonemia